Active layer monitoring in Antarctica: an overview of results from 2006 to 2015. (3rd July 2021) - Hrbáček, Filip; Vieira, Goncalo; Oliva, Marc; Balks, Megan; Guglielmin, Mauro; de Pablo, Miguel Ángel; Molina, Antonio; Ramos, Miguel; Goyanes, Gabriel; Meiklejohn, Ian; Abramov, Andrey; Demidov, Nikita; et al.
ABSTRACT: Monitoring of active layer thawing depth and active layer thickness (ALT), using mechanical pronging and continuous temperature data logging, has been undertaken under the Circumpolar Active Layer Monitoring – South (CALM-S) program at a range of sites across Antarctica. The objective of this study was to summarize key data from sites in different Antarctic regions from 2006 to 2015 to review the state of the active layer in Antarctica and the effectiveness of the CALM-S program. The data from 16 sites involving 8 CALM-S and another 8 boreholes across the Antarctic have been used in the study. Probing for thaw depth, while giving information on local spatial variability, often underestimates the maximum ALT of Antarctic soils compared to that determined using continuous temperature monitoring. The differences are likely to be caused by stones limiting probe penetration and the timing of probing not coinciding with the timing of maximum thaw, which varies between seasons. The information on the active layer depth is still sparse in many regions and the monitoring needs to be extended and continued to provide a better understanding of both spatial and temporal variability in Antarctic soil thermal properties.